The wilderness wanderings: a theo-liminal pedagogy for mind decolonisation in African Christianity - C. J. Kaunda (Acta Theologica)
This article argues that the current economic and political underdevelopment in the majority of African countries is a symptom of a profound metaphysical and intellectual crisis in the African person’s imagination and consciousness, a consequence of conceptual alienation wrought about mind colonialism. The process of decolonisation did not end with geopolitical liberation, but continues as liberation of the African mind and subjectivity. Reading this reality in light of the Exodus wilderness wanderings as theo-decolonial paradigm, the article suggests a theo-liminal pedagogy for engaging in the process of mind decolonisation.